The Influence of Configuration Parameters of the Planetary Drive of Crank Presses on its Dynamic and Energy-Consumption Characteristics - Vasilchenko, T.; Hrechanyi, O.; Shevchenko, I. (Science and Innovation, 2023)
Introduction. The planetary drive has been widely found in the activation systems of crank presses as it improves working conditions of friction units and reduces press metal consumption and energy consumption. Problem Statement. For studying the planetary motion of its main parts, it is advisable to consider its operation as four periods characterized by different patterns of changes in external loads and, consequently, different patterns of motion of core parts. The periods between switching the brakes when one link has not stopped, while other one starts moving is of the greatest interest. The problem of dynamic and energy-consumption parameters of the drive in transient conditions still remain a little open. Purpose. The purpose of this research is to qualitatively assess the influence of configuration parameters on the dynamics of the processes of switching and stopping the planetary drive. Material and Methods. The parameters of the experimental pilot plant, a model planetary drive with a nominal load of 400 kN, have been calculated. The minimum speed of the central gear has been estimated depending on the moments of inertia of the leading mass and the outer gear. The obtained dependences have been processed with the use of a standard mathematical apparatus. Results. It has been found that the energy-consumption and dynamic parameters of the drive are significantly influenced by such characteristics as moments of inertia and braking moments, while decreasing angular velocity of the drive flywheel does not depend on the moments of inertia of the stopped links. The rate of braking processes is determined by the elastic properties of the friction materials and the parameters of the brake springs, not by the parameters of compressed air outflow. Conclusions. The obtained analytical and graphical dependences have allowed not only qualitative, but also quantitative assessment of the influence of the parameters on the dynamics of processes. These recommendations can be used at the design stage, to select the optimal parameters of the drive with the predicted properties.